2002
DOI: 10.1016/s0735-1097(01)01772-7
|View full text |Cite
|
Sign up to set email alerts
|

Doppler myocardial imaging to evaluate the effectiveness of pacing sites in patients receiving biventricular pacing

Abstract: After BIV, LV performance improved significantly in all patients; however, the greatest improvement was found in patients paced at the most delayed site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
155
0
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(174 citation statements)
references
References 13 publications
11
155
0
8
Order By: Relevance
“…In a retrospective analysis where TDI assessment of mechanical activation was performed prior to CRT implantation, patients in whom the LV lead was situated at the site exhibiting the latest activation showed increased functional and echocardiographic improvements [15]. Superior response to CRT was also observed when the site of LMA was targeted using tissue synchronization imaging (TSI) [90], 3D echocardiography [91], and speckle tracking [92].…”
Section: Dyssynchrony Assessment and Identification Of The Site Of Lamentioning
confidence: 99%
“…In a retrospective analysis where TDI assessment of mechanical activation was performed prior to CRT implantation, patients in whom the LV lead was situated at the site exhibiting the latest activation showed increased functional and echocardiographic improvements [15]. Superior response to CRT was also observed when the site of LMA was targeted using tissue synchronization imaging (TSI) [90], 3D echocardiography [91], and speckle tracking [92].…”
Section: Dyssynchrony Assessment and Identification Of The Site Of Lamentioning
confidence: 99%
“…Tissue Doppler imaging (TDI) has been used to measure myocardial contraction and relaxation velocities, and to identify the presence of mechanical delays in dyssynchrony patients (12)(13)(14)(15). TDI measurements such as septal-to-posterior wall motion delay, time to peak systolic velocity, and the standard deviation (SD) of the time to peak velocity across the LV may predict clinical and echocardiographic response to CRT (13).…”
mentioning
confidence: 99%
“…This site is in the lateral wall in 35% of the cases, in the anterior and posterior walls in 26% and 23%, respectively, and rarely in the inferior and septal walls (16%) 29 .…”
Section: Where Should the Electrode Be Implanted?mentioning
confidence: 97%
“…And, in fact, Ansalone et al 29 have demonstrated that the best result was obtained in patients whose electrodes were implanted according to the site with the greatest electromechanical delay, determined on echocardiography.…”
Section: Lateral Wall Systolic Peakmentioning
confidence: 99%